Toward an International Migration Regime - Sachs, Jeffrey D. (The American economic review, 2016)
Few if any issues in public policy are as muddled and contentious as international migration. There is no international regime that establishes standards and principles for national migration policies other than in the case of refugees (migrants escaping persecution). My aim here is to describe some economic and ethical principles that may underpin an international migration regime.